2014
DOI: 10.1089/jpm.2013.0395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hospice Emergency Kit for Veterans and Their Caregivers: A Prospective Cohort Study

Abstract: Findings provide promising evidence that HEKs are a feasible and well-tolerated method for achieving timely relief of emergent symptoms in home hospice patients and possibly avoiding unwanted ED visits and hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…21,35 Increased caregiver confidence associated with Symptom Response Kits may explain the added effect of these kits on place of death in this study. 17,20 In contrast to previous literature, our primary analyses do not support an impact of the Yellow Folder or Symptom Response Kit on acute care utilization. Patients, caregivers, and health care providers have previously reported reduced rates of unscheduled interventions and hospital visits in emergency medication kit recipients, although these studies may be limited by recall bias.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…21,35 Increased caregiver confidence associated with Symptom Response Kits may explain the added effect of these kits on place of death in this study. 17,20 In contrast to previous literature, our primary analyses do not support an impact of the Yellow Folder or Symptom Response Kit on acute care utilization. Patients, caregivers, and health care providers have previously reported reduced rates of unscheduled interventions and hospital visits in emergency medication kit recipients, although these studies may be limited by recall bias.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients, caregivers, and health care providers have previously reported reduced rates of unscheduled interventions and hospital visits in emergency medication kit recipients, although these studies may be limited by recall bias. 15,17,18,20,23 Although our sensitivity analyses demonstrated reduced hospital utilization rates among intervention recipients when we focused on the period preceding death, these post hoc analyses should be viewed as hypothesis generating.…”
Section: Discussionmentioning
confidence: 90%
“…16 To make dying at home more feasible, prevention of short admissions in the final days of life was recommended. 21 Notably, there are services and practical suggestions (such as mobile palliative care teams, hospice emergency kits with instructions in their use for family members 22,23 ) that enable families to care for the dying at home. Moreover, General Practitioners (GPs) play a central role in providing continuity of care and helping to avoid unnecessary hospitalizations at the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study revealed that lacking medical equipment, e.g., specific medication for palliative—not emergency—care, also causes challenging situations. In literature, some studies focussing on the use of emergency medicine kits in home hospice patients are indicating that these medications kits could be helpful to provide timely symptom relief and may diminish the need for prehospital emergency care [13, 14]. These findings add some new aspects to improve prehospital emergency care in patients with advanced incurable diseases in their familiar home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies showed that some emergency department visits might be avoidable and are related to some such as pain medication refills or constipation [12]. The use of emergency medicine kits in home hospice patients seems to be helpful and might provide a timely symptom relief and may diminish the need for prehospital emergency care [13, 14]. Nevertheless, there are still unavoidable emergency department visits related to infections or neurologic events.…”
Section: Introductionmentioning
confidence: 99%